1985
DOI: 10.1021/jo00213a048
|View full text |Cite
|
Sign up to set email alerts
|

Applications of cyclopropylboranes in organic synthesis. 1. A stereocontrolled route to substituted cyclopropanol derivatives

Abstract: thiobenzophenone-derived cycloadducts were obtained relative to the amount resulting from a trap with dimethyl fumarate. a fellowship, K.S. and H.B. to UCSB for fellowships, and O.W. to the Swiss National Fund for financial support during postdoctoral studies conducted at UCSB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 1 publication
(2 reference statements)
1
22
1
Order By: Relevance
“…Ti(O-i-Pr) 4 method, perhaps because the Ti method is heterogeneous, whereas the present method is homogeneous. Ti(O-i-Pr) 4 method, perhaps because the Ti method is heterogeneous, whereas the present method is homogeneous.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Ti(O-i-Pr) 4 method, perhaps because the Ti method is heterogeneous, whereas the present method is homogeneous. Ti(O-i-Pr) 4 method, perhaps because the Ti method is heterogeneous, whereas the present method is homogeneous.…”
mentioning
confidence: 84%
“…11 [e] None of the Co and Ni catalysts, which we examined, 12 Fe(dbm) 3 and FeCl 2 (dppe) catalysts were also effective, however, the reaction was a little sluggish. 17 [d] Even MeMgBr worked as a reducing reagent in contrast to the Ti(O-i-Pr) 4 catalyzed method, wherein MeMgBr is adopted only for gem-dibromocyclopropanes. 17 [d] Even MeMgBr worked as a reducing reagent in contrast to the Ti(O-i-Pr) 4 catalyzed method, wherein MeMgBr is adopted only for gem-dibromocyclopropanes.…”
mentioning
confidence: 99%
“…[14] This process has been utilized successfully in the alkylation of α-haloalkylmetals (e.g., M ϭ Mg, [15] Zn, [16] B, [17] or Cu [18] ) and allows the facile introduction of an alkyl group to the organometallic reagents. This process enables complex metallic reagents to be prepared from relatively simple and easily accessible organometallic species.…”
Section: Methodsmentioning
confidence: 99%
“…13 They reported that various substituted cyclopropanols can be synthesized by the reaction of gemlithiobromocyclopropanes with alkylboranes such as trialkylboranes or catecholborane and exploiting 1,2-migration of an alkyl group or hydrogen from boron to carbon. We decided to examine this protocol using alkynylboranes as the boron component.…”
Section: Methodsmentioning
confidence: 99%
“…In the reaction of 7,7-dibromobicyclo-[4.1.0]heptane 12 (n=1), only one diastereomer was obtained, whose stereochemistry was assigned as the endo-alkynyl isomer as shown in 14a by analogy with the results of Danheiser. 13 In the case of the reaction of 8,8-dibromobicyclo[5.1.0]octane 12 (n=2), a mixture of endo and exo isomers were obtained. Furthermore, the products, in particular the exo isomers 15c (n=2, R=Ph) and 15d (n=2, R=n-Bu), were insufficiently stable to be purified and the crude products were directly silylated with TBSOTf and Et 3 N to give the separable mixture of endo isomers 16c,d and exo isomers 17c,d.…”
Section: Methodsmentioning
confidence: 99%